2020
DOI: 10.3389/fimmu.2020.578654
|View full text |Cite
|
Sign up to set email alerts
|

The Antidepressant Mirtazapine Activates Hepatic Macrophages, Facilitating Pathogen Clearance While Limiting Tissue Damage in Mice

Abstract: Background and Aims: Mirtazapine is an atypical antidepressant with antagonist activity for serotonin and histamine receptors. Clinical and experimental evidence suggests that, in addition to treating depression, mirtazapine also alters liver innate immunity and suppresses immune-driven hepatic macrophage activation. Liver macrophages, Kupffer cells, represent the largest collection of fixed macrophages in the body and are critical in regulating hepatic immunity. In addition to their capacity to regulate infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Furthermore, secretion of the anti-inflammatory cytokine IL-4, but not IL-10, was increased post in vitro stimulation. These data are in agreement with previous work of the group showing effects of mirtazapine treatment on liver immunity and suppression of liver inflammation ( 52 ).…”
Section: Suppression Of B Cell-derived Pro-inflammatory Cytokine Prod...supporting
confidence: 93%
“…Furthermore, secretion of the anti-inflammatory cytokine IL-4, but not IL-10, was increased post in vitro stimulation. These data are in agreement with previous work of the group showing effects of mirtazapine treatment on liver immunity and suppression of liver inflammation ( 52 ).…”
Section: Suppression Of B Cell-derived Pro-inflammatory Cytokine Prod...supporting
confidence: 93%
“…Mirtazapine is considered an antagonist of 5HT2A, 5HT2C and 5HT3 serotonin receptors, not 5HT1A receptors ( 53 ). Moreover, B cells express 5HT2A and 5HT3 receptors ( 54 , 55 ).We have previously reported that mirtazapine treatment does not alter total hepatic serotonin levels ( 15 , 27 ). However, mirtazapine treatment may potentially alter hepatic B cell responses by blocking signaling through 5HT2A, 5HT2C and 5HT3 serotonin receptor subtypes, or by augmenting signaling through other serotonin receptor subtypes (including 5HT1A) by enhancing the local availability of serotonin ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…All procedures were approved by the University of Calgary Animal Care Committee (#AC18-0154) and performed as per the guidelines of the Canadian Council on Animal Care. The fewest number of mice were used in each experiment to ensure scientific validity and were determined based on our significant previous work with this mouse model and techniques used ( 15 , 26 , 27 ). The number of animals used for individual experiments are reported in corresponding figure legends.…”
Section: Methodsmentioning
confidence: 99%
“…After 8 weeks of treatment, MTZ significantly outperformed a placebo in the preventive treatment of persistent tension-type headaches Bendtsen and Jensen ( 2004 ) Obsessive–compulsive disorder The effectiveness of MTZ in patients with OCD has been examined in two randomized, controlled trials. MTZ’s effects on OCD have been documented to be effective in OCD as a pharmacotherapy Koran et al ( 2005 ) In a pilot trial, the effects of citalopram and MTZ in patients with OCD who did not also have comorbid depression When MTZ was combined with citalopram, they discovered a faster onset of responsive action in OCD symptoms and decreased undesirable side effects Pallanti et al ( 2004 ) The potential protective effects of MTZ on diseases other than CNS-related disorders Liver diseases High-fat diet mice model Obese mice treated with MTZ had reduced levels of body weight, serum TG and AST levels The treated mice had lower blood glucose levels and increased insulin sensitivity and glucose transporter 4 expression levels Wu et al ( 2020 ) Immune-mediated liver disease MTZ rapidly shifts the hepatic B-cell populations and functional cytokine signatures of mice Treatment with MTZ increases the retention of innate-like B cells that express CXCR3, producing more anti-inflammatory cytokines Almishri et al ( 2021 ) IV infection with a pathogenic strain of S. aureus in mice MTZ affects liver innate immunity and inhibits immune-driven activation of hepatic macrophages Treatment with MTZ may have beneficial effects on sepsis, and it significantly decreases the risk of hepatic abscess formation Davis et al ( 2020 ) Liver fibrosis induced by thioacetamide in mice MTZ treatment ameliorated TAA-induced liver fibrosis by lowering portal BP, liver procollagen I content, and α-SMA expression MTZ-treated animals had significantly less hepatic collagen accumulation. MTZ decreased the levels of protein kinase C, TGF-β1, phosphorylated Smad3, p-ERK1/2 MTZ significantly reduced oxidative stress, by declining hepatic lipid peroxidation and NADPH oxidase 1 and increased GSH content El-Tanbouly et al ( 2017 ) Kidney diseases Diabetic nephropathy in rats …”
Section: Pharmacological Update Of Mtzmentioning
confidence: 99%